17-4PH stainless steel fastener for high salt fog open-air marine coupling - Angang Cao; Tao Yu; Yigui Lu; Wei Li (PLoS ONE, 2025)
The C01 type diaphragm coupling demonstrates effective performance in high-concentration seawater salt fog environments. However, the fastener material for this coupling must possess high mechanical properties and strong resistance to seawater corrosion. This study evaluates the suitability of 17−4 precipitation hardening (PH) stainless steel for diaphragm coupling fasteners through a series of tests, including pitting corrosion, crevice corrosion, stress corrosion, fatigue, galvanic corrosion, and cyclic immersion. The results show that the weight loss of 17−4PH stainless steel sample is 13.71% after pitting test and 7.73% after crevice test. However, after stress corrosion, fatigue, and galvanic corrosion tests, the 17−4PH stainless steel sample exhibits minimal corrosion sensitivity. These findings indicate that 17−4PH stainless steel is particularly susceptible to crevice and pitting corrosion. Consequently, 17−4PH shows no pronounced corrosion sensitivity within 15 days of exposure, supporting its provisional use in marine couplings subject to short-term salt fog environments, with caution regarding crevice corrosion risks. 17−4PH is suitable for marine coupling fasteners when combined with passivation, crevice sealing, or design optimization to mitigate pitting and crevice corrosion. Overall, this study provides an experimental basis for the application of 17−4PH stainless steel in diaphragm couplings under high salt fog environments.